A novel small-molecule inhibitor of the human papillomavirus E6-p53 interaction that reactivates p53 function and blocks cancer cells growth. (1st February 2020) - Celegato, Marta; Messa, Lorenzo; Goracci, Laura; Mercorelli, Beatrice; Bertagnin, Chiara; Spyrakis, Francesca; Suarez, Irina; Cousido-Siah, Alexandra; Travé, Gilles; Banks, Lawrence; Cruciani, Gabriele; Palù, Giorgio; et al.
Abstract: Despite prophylactic vaccination campaigns, human papillomavirus (HPV)-induced cancers still represent a major medical issue for global population, thus specific anti-HPV drugs are needed. Since the ability of HPV E6 oncoprotein to promote p53 degradation is linked to tumor progression, E6 has been proposed as an ideal target for cancer treatment. Using the crystal structure of the E6/E6AP/p53 complex, we performed an in silico screening of small-molecule libraries against a highly conserved alpha-helix in the N-terminal domain of E6 involved in the E6-p53 interaction. We discovered a compound able to inhibit the E6-mediated degradation of p53 through disruption of E6-p53 binding both in vitro and in cells. This compound could restore p53 intracellular levels and transcriptional activity, reduce the viability and proliferation of HPV-positive cancer cells, and block 3D cervospheres formation. Mechanistic studies revealed that the compound anti-tumor activity mainly relies on induction of cell cycle arrest and senescence. Our data demonstrate that the disruption of the direct E6-p53 interaction can be obtained with a small-molecule compound leading to specific antitumoral activity in HPV-positive cancer cells and thus represents a new approach for anti-HPV drug development. Highlights: The HR-HPV E6-p53 direct interaction can be inhibited by small molecules. A lead small molecule (compound 12) inhibits the E6-mediated degradation of p53. Compound 12 exerts specific anti-tumor activity in HPV-positive cervical cancer cells. Rescue of p53 by compound 12 induces cell cycle arrest and senescence. Compound 12 can be the basis for the development of specific anti-HPV drugs.